2016
DOI: 10.1159/000446423
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Diving Mask on Intraocular Pressure in a Healthy Population

Abstract: Purpose: Swimming goggles increase the intraocular pressure (IOP) via the periorbital frame pressure and suction effect. In comparison, diving masks have a larger frame rim and incorporate the nose. The exact effect(s) of diving masks on IOP is unknown. This study evaluates the influence of diving masks on IOP in normal, healthy subjects. Methods: Tonometry was performed in both eyes of all subjects with an AVIA®Tono-Pen by a single investigator. Measurements were taken at baseline without the divin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Scuba diving is a kind of underwater diving where the divers breathe underwater with the help of self-contained breathing equipment. Contrary to swimming goggles, the diving mask has not been found to induce any increase in IOP (Goenadi et al 2016). As early as the 1970s, Kalthoff et al (1975) reported that under excessive pressures of 2 and 4 atm, the IOP decreased by 2-3 mmHg.…”
Section: Types Of Dynamic Exercises With Potential Adverse Effects Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Scuba diving is a kind of underwater diving where the divers breathe underwater with the help of self-contained breathing equipment. Contrary to swimming goggles, the diving mask has not been found to induce any increase in IOP (Goenadi et al 2016). As early as the 1970s, Kalthoff et al (1975) reported that under excessive pressures of 2 and 4 atm, the IOP decreased by 2-3 mmHg.…”
Section: Types Of Dynamic Exercises With Potential Adverse Effects Onmentioning
confidence: 99%
“…Contrary to swimming goggles, the diving mask has not been found to induce any increase in IOP (Goenadi et al. ). As early as the 1970s, Kalthoff et al.…”
Section: Physical Exercise and Iop Controlmentioning
confidence: 99%
“…To provide a watertight seal while diving, diving masks need to fit tightly against the periorbital region, with the potential risk of raising the IOP. Goenadi et al explored this possible relationship by studying the effect of dive mask wearing on IOP, in a cohort of 40 eyes from 20 healthy volunteers ( 32 ). The AVIA Tono-Pen (Reichert Inc., NY, United States) was used to measure IOP at baseline with and without the diving mask (with the lenses removed) worn.…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations are expected in SCUBA diving, and it is the most likely hypothesis to explain our results. Other hypotheses were also considered as being unlikely with our experimental setting: Goenadi et al suggest that in contrast with swimming goggles, diving masks can induce small decrease of 0.43 mmHg in IOP after diving [64]. All divers wore diving masks (different from swimming goggles), respected mask pressure normalization during diving, and no mask squeeze was observed.…”
Section: Intraocular Pressurementioning
confidence: 85%
“…Goenadi et al suggest that in contrast with swimming goggles, diving masks can induce small decrease of 0.43 mmHg in IOP after diving [ 64 ]. All divers wore diving masks (different from swimming goggles), respected mask pressure normalization during diving, and no mask squeeze was observed.…”
Section: Discussionmentioning
confidence: 99%